Love, Sex, and Satisfaction in On-Again/Off-Again Relationships: Exploring What Might Make These Relationships Alluring. (7th June 2017) - Dailey, René M.; Powell, Alexander
Abstract : The current study explored positive relational qualities — love, need satisfaction, sexual satisfaction— to better understand what might be alluring to on-again/off-again (cyclical) partners given that they typically report lower relational quality and functioning than non-cyclical partners (i.e., those who have not broken up and renewed). A sample of 558 young adults in current romantic relationships (27.6% in cyclical relationships) reported on Sternberg's (1997 ) three love components (intimacy, passion, and commitment), relationship need satisfaction (e.g., companionship, emotional involvement), and their sexual satisfaction. Results supported the bulk of research showing cyclical partners report lower relational quality — cyclical partners reported less love, need satisfaction, and sexual satisfaction. A pattern of findings regarding passion and need satisfaction regarding sexual and physical intimacy, however, suggests that cyclical partners might value the physical component of relationships more, and further, that passion might be more strongly related to global satisfaction as compared to non-cyclical partners. Overall, the value of this study is not in what differences were found but in ruling out certain explanations of what perpetuates cycling in young adult relationships. The current findings suggest the reasons individuals return to less satisfying relationships is complex and might require novel theoretical models.